Challenges, opportunities and barriers to sustainable transport development in functional urban areas - Wolny, Ada; Ogryzek, Marek; Źróbek, Ryszard (International Conference “Environmental Engineering”, 2017)
The process of identifying urban areas in OECD countries uses population density to identify urban cores, and travel-to-work flows to identify the hinterlands as the “worker catchment area” of the urban labour market, outside the densely inhabited core. As the travel-to-work analysis seems to be an important issue for creating coherent functional urban areas, the main determinants of daily commuting in a subregional scale should be investigated. There is a common opinion, that residents of the suburbs are bound to use individual forms of transportation, and public transport does not meet their needs. That is why the aim of this research is to identify the main challenges, opportunities and barriers to sustainable transport development in functional urban areas, in order to avoid the adverse effects of urbanisation. For the purpose of the article, a comparative analysis for selected Polish functional urban areas was conducted, and both short term and long-term prospects of transport development are depicted. The article includes statistical, spatial and descriptive analyses based on Central Statistical Office data, Regional Operational Programmes for 2014–2020, made for the Polish provinces, as well as selected development strategies, due to intermunicipal cooperation within delimited functional urban areas. As a result, on the basis of the compared and transformed information, the sustainable development scenarios for a selected functional urban area are built.
Keywords: functional urban areas; transport; sustainable development